Estado nutricional do abacaxizeiro „Pérola‟ adubado com NPK e enxofre - Rodrigues, João Batista Belarmino (2016)
Although is important there are no basic information about fertilization and mineral nutrition, at example of response curves and critical levels for the 'Pérola' pineapple in the main producing municipalities in the Paraiba State. The objective of this study was to evaluate the effects of application of N, P, K and S rates on the nutritional status, and to determine the critical levels of their nutrients for the 'Pérola' pineapple grown in Argisol of the municipality of Itapororoca, PB. The experiment was conducted under rainfed conditions between December of 2014 and December of 2015, in a randomized block design with 26 treatments and three replications. The treatments were arranged in an experimental matrix Plan Puebla III modified and resulted from the combination of five N rates (50, 300, 500, 700 and 950 kg/ha - urea), five K rates (50, 300, 500, 700 and 950 kg/ha K2O - potassium sulfate), five P rates (20, 120, 200, 280 and 380 kg/ha P2O5 - MAP) and five S rates (20, 120, 200, 280 and 380 kg / ha - potassium sulphate). The plantlets of cv. Pérola were planted at spacings 0.80 × 0.40 ×0.40 m under double-row systems. The following variables were evaluated at the time of floral induction (345 days after planting - dap): fresh weight of leaf 'D' (FWL); content and accumulation of N, P, K and S on the leaf 'D'; pH values and levels of P, K, S and organic matter in soil (0-20 cm). Also, were estimated critical levels of N, P, K and S. By results, was found that the increase in N rates acidified soil, but did not influence, as well as the doses of P, K and S, the organic matter level; however, the levels of P, K and S in the soil increased with doses of their nutrients. The doses of N, P, K and S increased the fresh weight of leaf 'D', although the responses to P and S were conditioned to the doses of N and K, respectively. Doses of N and K increased the levels of N and K and the accumulation of N; however, the N rates decreased the accumulation of K. P concentrations increased with N and K rates, while accumulations have increased with P and S rates. Nutrient rates did not affect the nutritional status of xvi plant on the S. The critical levels of N, P, K and S found for the pineapple 'Pearl' were 17.3; 0.94; 34.9 and 1.5 g/kg, respectively.